A Young Female with Pain and Weakness of Lower Limb - Reza, Ishrat Binte; Hossain, Homayra Tahseen; Zarin, Esrat; Miah, Titu; Alam, SA Nurul; Ahasan, HAM Nazmul (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Abstract not available J Bangladesh Coll Phys Surg 2017; 35(4): 200-201